Efficient current injection device for harmonic reduction of three‐phase controlled converters - Ali Mohamed Eltamaly (IET Circuits, Devices and Systems)
Third harmonic current injection technique is one of the best options for harmonic reduction of three‐phase controlled/uncontrolled converters. Injecting third harmonics current from dc‐bus to the line current reduces its harmonic contents. Minimum THD for any firing angle of controlled converter is function in phase‐angle and amplitude of harmonic injection current that can be controlled by single‐phase controlled and boost converters, respectively. This scheme is used with three bidirectional switches as harmonic injection device to circulate the injection current to supply currents. This scheme is compared with the state‐of‐the‐art system using zigzag transformer. A novel mathematical analysis for the proposed scheme and state‐of‐the‐art scheme is introduced. The mathematical analysis introduces the optimum values for components on the harmonic injection path at minimum THD and the corresponding efficiency of each scheme. The two schemes under study have been simulated using PSIM program. Two lab prototypes for these two schemes have been implemented. Mathematical, simulation, and experimental results for these two schemes have been introduced, compared, and discussed. The results show the superiority of the proposed scheme.